Proposition of patient stratification and parameter setting for mechanical traction in patients with LBP - Michał Igor Dylewski; Monika Dylewska; Alicja Kasprzak; Roman Bednorz; Jakub Maliszewski; Krzysztof Cygoń; Joanna Boczula (Kazimierz Wielki University, 2020)
Mechanical traction of the lumbar spine remains a procedure very willingly used by therapists in many countries of the world, despite at least equivocal scientific evidence. One of the problems reducing its effectiveness is the problem with the selection of patients for therapy as well as selecting the therapeutic goals and treatment parameters for the patient in an individualized and, at the same time, repeatable manner. In this work, the authors presented such a model developed as part of Research and Development works carried out at the Leśny Dom Seniora in Piastów.